Similarities and differences between post-traumatic stress disorder and major depressive disorder: Evidence from task-evoked functional magnetic resonance imaging meta-analysis - Wang, Zuxing; He, Danmei; Yang, Lin; Wang, Peijia; Xiao, Jun; Zou, Zhili; Min, Wenjiao; He, Ying; Yuan, Cui; Zhu, Hongru; Robinson, Oliver J. (Journal of affective disorders, 2024)
Post-traumatic stress disorder (PTSD) and major depressive disorder (MDD) are psychiatric disorders that can present with overlapping symptoms and shared risk factors. However, the extent to which these disorders share common underlying neuropathological mechanisms remains unclear. To investigate the similarities and differences in task-evoked brain activation patterns between patients with PTSD and MDD. A coordinate-based meta-analysis was conducted across 35 PTSD studies (564 patients and 543 healthy controls) and 125 MDD studies (4049 patients and 4170 healthy controls) using anisotropic effect-size signed differential mapping software. Both PTSD and MDD patients exhibited increased neural activation in the bilateral inferior frontal gyrus. However, PTSD patients showed increased neural activation in the right insula, left supplementary motor area extending to median cingulate gyrus and superior frontal gyrus (SFG), and left fusiform gyrus, and decreased neural activation in the right posterior cingulate gyrus, right middle temporal gyrus, right paracentral lobule, and right inferior parietal gyrus relative to MDD patients. Our meta-analysis suggests that PTSD and MDD share some similar patterns of brain activation, but also have distinct neural signatures. These findings contribute to our understanding of the potential neuropathology underlying these disorders and may inform the development of more targeted and effective treatment and intervention strategies. Moreover, these results may provide useful neuroimaging targets for the differential diagnosis of MDD and PTSD. •A first meta-analysis to investigate the common and distinct neural activation patterns of patients with MDD and PTSD•Common and distinct neural activation patterns in patients with MDD and PTSD were found.•Potential neuroimaging targets for the diagnosis and differentiation of PTSD and MDD were found.